2017
DOI: 10.3390/rs9080838
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Sentinel-2 and Landsat-8 Data to Map Sucessional Forest Stages in a Subtropical Forest in Southern Brazil

Abstract: Studies designed to discriminate different successional forest stages play a strategic role in forest management, forest policy and environmental conservation in tropical environments. The discrimination of different successional forest stages is still a challenge due to the spectral similarity among the concerned classes. Considering this, the objective of this paper was to investigate the performance of Sentinel-2 and Landsat-8 data for discriminating different successional forest stages of a patch located i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 86 publications
(82 reference statements)
9
58
0
3
Order By: Relevance
“…The time-series Landsat-8 and Sentinel-2A data, covering the crucial growing and leaf-off seasons of the forest, could provide phenological information to improve the discrimination between different forest types. This result is in good agreement with the findings of [19,50], who summarized that time-series images can obtain much higher accuracy of mapping tropical forest types. Macander et al [53] have also used seasonal composite Landsat imagery and the random forest method for plant type cover mapping and found that multi-temporal imagery improved cover classification.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The time-series Landsat-8 and Sentinel-2A data, covering the crucial growing and leaf-off seasons of the forest, could provide phenological information to improve the discrimination between different forest types. This result is in good agreement with the findings of [19,50], who summarized that time-series images can obtain much higher accuracy of mapping tropical forest types. Macander et al [53] have also used seasonal composite Landsat imagery and the random forest method for plant type cover mapping and found that multi-temporal imagery improved cover classification.…”
Section: Discussionsupporting
confidence: 82%
“…Seen from the experimental results of forest type identification by using only Landsat-8 and Sentinel-2A imagery, we concluded that Sentinel-2A images can achieve a higher overall accuracy due to its high spatial resolution (Tables 9 and 10). This result is the same as [50], who concluded that the classification using Sentinel-2 images performed better than Landsat-8 data.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations